A phase II study of preoperative capecitabine in women with operable hormone receptor positive breast cancer. (27th January 2014) - Tolaney, Sara M.; Jeong, Joon; Guo, Hao; Brock, Jane; Morganstern, Daniel; Come, Steven E.; Golshan, Mehra; Bellon, Jennifer; Winer, Eric P.; Krop, Ian E.
Abstract Conventional preoperative chemotherapy regimens have only limited efficacy in hormone receptor positive (HR+) breast cancer and new approaches are needed. We hypothesized that capecitabine, which is effective in metastatic breast cancer, may be an active preoperative treatment for HR+ breast cancer. Women with HR+, HER2‐negative operable breast cancer received capecitabine, 2000 mg/m2 daily in divided doses for 14 days, followed by a 7‐day rest period. Treatment was repeated every 21 days for a total of four cycles. The primary endpoint of the study was to determine the rate of pathological complete response (pCR). Because of slow accrual, the study was closed after 24 patients were enrolled. Three patients had a complete clinical response, and eight patients had a partial clinical response, for an overall clinical response rate of 45.8%. There were no cases of pCR. Of the 22 patients who had pathological response assessment by the Miller–Payne grading system, there were six grade 3 responses, and no grade 4 or 5 responses. Toxicity was manageable: the only grade 3 toxicities observed were one case each of diarrhea, palmar plantar erythrodysesthesia, hypokalemia, and mucositis. There was no association between baseline levels, or change in level from baseline to cycle 1, or from baseline to time of surgery, of thymidine phosphorylase (TYMP), thymidylate synthase (TYMS), dihydropyrimidine dehydrogenase (DPYD), or Ki67 and pathological, clinical, or radiographic response. Preoperative capecitabine is a well‐tolerated regimen, but appears not lead to pCR when used as monotherapy in HR+ breast cancer.